Age and emplacement of the Permian–Jurassic Menghai batholith, Western Yunnan, China. Issue 8 (11th June 2017) - Catlos, Elizabeth J.; Reyes, Enrique; Brookfield, Michael; Stockli, Daniel F.
ABSTRACT: The Menghai batholith (Yunnan Province, China) is the southern extension of the ~370 km long Lincang granite body that syntectonically intruded the collisional zone between Gondwana (Baoshan block) and Laurasia (Simao block) terranes during closure of the Palaeo-Tethyan Ocean. Eight Menghai granodiorites were analysed across an ~45 km E–W transect from the pluton's central region to eastern perimeter. Each rock was imaged in cathodoluminescence and geochemically analysed for major and trace elements. A minimum 30 zircons per sample were dated using laser ablation inductively coupled plasma–mass spectrometry. Samples are peraluminous to strongly peraluminous, magnesian, calcic or calc-alkalic granodiorites. Trace element suggest a high pressure (12–15 kbar) low clay source with >20–30% volume interaction with basalt. Crustal anatexis was likely related to post-collisional lithosphere delamination and upwelling of hot asthenosphere, forming large-volume melts. Zircon ages ( 207 Pb– 206 Pb and 238 U– 206 Pb) range from 3234 ± 42 to 171.7 ± 5.4 Ma (±2 σ ). Inherited zircon ages include the Palaeoarchaean–Neoarchaean (average 2938 ± 27 Ma, n  = 8 ages), Lüliang (2254 ± 38 Ma, n   = 7), Changcheng–Jixianian (1274 ± 47 Ma, n   = 33), Qinbaikou (963 ± 29 Ma, n   = 7), Nanhua (787 ± 24 Ma, n   = 7), Sinian (595.4 ± 12.2 Ma, n   = 14), Qilian (452.2 ± 8.7 Ma, n   = 24) and Tienshan (358.9 ± 12.4 Ma, n   = 5). The presence of these ages decrease from the batholith's central portion (>50% ages) to eastern perimeter (2–16% ages), as the rocks appear progressively metamorphosed. The distribution of U/Th ratio suggests inherited zircons are Carboniferous (317.6 ± 5.7 Ma) and older and crystallization ages span the Permian to Early Jurassic. The average and youngest zircon age per sample decreases from the centre of the batholith to its eastern perimeter, from 226.8 ± 8.8 and 210.7 ± 3.3 to 211.8 ± 5.7 and 171.0 ± 5.4 Ma, respectively. If recorded by syntectonic zircon crystallization, collision and closure of a branch of the Palaeo-Tethyan Ocean occurred here over an ~100 million years time period from the Permian (281.0 ± 13.0 Ma) to Jurassic (171.5 ± 5.4 Ma).